ETIKA KONSUMSI DALAM PERSPEKTIF EKONOMI ISLAM - Bahri S., Andi (State Institute of Islamic Studies (IAIN) Palu, 2014)
ThisÂ paper deals withÂ consumptionÂ behaviorÂ in society;Â howÂ toÂ consume asÂ recommendedÂ by Islam;Â andÂ howÂ shouldÂ Â consumptionÂ behaviorÂ in the view ofÂ Islamic economics. Based on the results of the analysis, we concluded as follows:Â 1) Consumption behaviorÂ shouldÂ pay attention toÂ the aspects of theÂ categories of needs asprimaryÂ needs,Â secondary needs and tertiary needsÂ Â in accordanceÂ withÂ the spirit ofÂ al-maqÄá¹£dÂ al-syarÄ«â€™ah.Â In theÂ view ofÂ Islam, consumption behavior should avoid isrÄf andÂ tabÅ¼Ä«rÂ behaviorÂ in usingÂ their income toÂ meet their life needs. In the aspect of comsuming any kind of food, theÂ MuslimsÂ shouldÂ Â always comsume theÂ Â halalÂ Â andÂ theÂ toyyibÂ food.Â Consumption behaviorÂ inÂ IslamicÂ economics aims at achieving bothÂ the aspect ofÂ material and theÂ aspect ofÂ spriruality,Â these two aspectsÂ will be achievedÂ by maximizing the value of the use ofÂ eachÂ itemÂ inÂ consumption.Kata kunci: Â Perilaku konsumsi, kebutuhan, keingingan, ekonomi Islam